International marketing - Zou, Shaoming; Fu, Huifen (Emerald, 2011)
The global financial crisis has accelerated the shift of economic power from the West to the East. The emerging markets have become the main engine of global economic growth and firms from emerging markets are playing an increasingly important role in global competition. This volume of Advances in International Marketing is focused on issues that have been largely ignored by the main stream literature in international marketing to emerging markets and by firms from emerging markets. The papers presented report a variety of studies examining: international marketing behaviour of firms from emerging markets; market environments and consumer behaviour in emerging markets; and MNCs international marketing in emerging markets. Collectively they offer significant insight into emerging markets and point to new directions for future research.
Keywords: Export marketing.; elektronické knihy; electronic books